CRISPR-Based Genome Editing for Nutrient Enrichment in Crops: A Promising Approach Toward Global Food Security - Kumar, Dileep; Yadav, Anurag; Ahmad, Rumana; Dwivedi, Upendra Nath; Yadav, Kusum (Frontiers in Genetics, 2022)
The global malnutrition burden imparts long-term developmental, economic, social, and medical consequences to individuals, communities, and countries. The current developments in biotechnology have infused biofortification in several food crops to fight malnutrition. However, these methods are not sustainable and suffer from several limitations, which are being solved by the CRISPR-Cas-based system of genome editing. The pin-pointed approach of CRISPR-based genome editing has made it a top-notch method due to targeted gene editing, thus making it free from ethical issues faced by transgenic crops. The CRISPR-Cas genome-editing tool has been extensively used in crop improvement programs due to its more straightforward design, low methodology cost, high efficiency, good reproducibility, and quick cycle. The system is now being utilized in the biofortification of cereal crops such as rice, wheat, barley, and maize, including vegetable crops such as potato and tomato. The CRISPR-Cas-based crop genome editing has been utilized in imparting/producing qualitative enhancement in aroma, shelf life, sweetness, and quantitative improvement in starch, protein, gamma-aminobutyric acid (GABA), oleic acid, anthocyanin, phytic acid, gluten, and steroidal glycoalkaloid contents. Some varieties have even been modified to become disease and stress-resistant. Thus, the present review critically discusses CRISPR-Cas genome editing-based biofortification of crops for imparting nutraceutical properties.